2010
DOI: 10.1521/jsyt.2010.29.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Trauma on Therapists: Vicarious Resilience and Related Concepts in Training

Abstract: An integrative training framework articulating multiple perspectives on the impact of trauma work is offered with a training/supervision exercise to address the complex and systemic relationships that affect therapists in both positive and negative manners. The concepts of vicarious trauma, vicarious resilience, compassion fatigue, resilience, posttraumatic growth, altruism born of suffering, and reciprocity are reviewed. The paper highlights the importance of vicarious resilience as a dimension of experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 19 publications
2
62
1
Order By: Relevance
“…Sider's (2006) approach is similar to what Hernandez, Gangsei, and Engstrom (2007) described as vicarious resilience -the valuable lessons a therapist can glean from watching clients successfully maneuver traumatic events. In a later study conducted by Hernandez, Engstrom, and Gangsei (2010), vicarious resilience is identified as a mitigating factor against compassion fatigue for caregivers working with traumatized victims. Hence, professional caregivers can reduce their own compassion fatigue if they learn the keys to overcoming horrific trauma by watching and learning from their clients.…”
Section: Definitions Of Stress Related Prevention Strategies and Promentioning
confidence: 99%
“…Sider's (2006) approach is similar to what Hernandez, Gangsei, and Engstrom (2007) described as vicarious resilience -the valuable lessons a therapist can glean from watching clients successfully maneuver traumatic events. In a later study conducted by Hernandez, Engstrom, and Gangsei (2010), vicarious resilience is identified as a mitigating factor against compassion fatigue for caregivers working with traumatized victims. Hence, professional caregivers can reduce their own compassion fatigue if they learn the keys to overcoming horrific trauma by watching and learning from their clients.…”
Section: Definitions Of Stress Related Prevention Strategies and Promentioning
confidence: 99%
“…Arnold et al (2005) state that the therapist's growth occurs in these same three areas following exposure to client trauma. Though literature references the existence of therapist's personal growth, there is also some acknowledgement of significant limitations in the research (Arnold et al, 2005;Kottler & Smart, 2006;Hernandez et al, 2007;Engstrom et al, 2008;Hernandez et al, 2010). Kottler and Smart (2006) proposed that this may be due to a sense of shame that, as therapists, we should not personally benefit from our clients.…”
Section: Resilience In Individual Therapymentioning
confidence: 99%
“…Despite this, there is growing evidence to suggest that working with resilient clients can strengthen a worker's own resilience. Hernandez, Engstrom, and Gangsei (2010) explored the idea of reciprocity in therapeutic relationships and described how witnessing clients overcoming adversity can change a therapist's "attitudes, emotions and behavior in ways that the authors conceptualized as manifesting vicarious resilience" (p. 72). Hence, the concept of vicarious resilience offers a unique perspective on how resilience in practitioners who are working daily with traumatized clients can be developed by proxy, through participation in the lives of resilient survivors of trauma and abuse (Hernandez, Gangsei, & Engstrom, 2007;Alvarez & Hurley, 2010).…”
Section: Resilience and Child Protectionmentioning
confidence: 99%